Pengaruh Media Augmented Reality Terhadap Pengenalan Kosakata Bahasa Arab Anak Usia 5-6 Tahun di TKIT Mukti Tama Kota Jambi - Nia Rismala; Asih Nur Ismiatun; Kasmiati . (CV. ITTC INDONESIA, 2026)
The ability to recognize Arabic vocabulary in children aged 5-6 years at TKIT Mukti Tama is still relatively low. Children experience difficulties in pronouncing vocabulary, understanding meanings, as well as remembering and using the learned words in simple contexts. In addition, the use of conventional learning media makes the learning process less engaging and less effective in providing concrete and meaningful learning experiences for children. This condition indicates the need for more innovative, interactive, and developmentally appropriate learning media, one of which is augmented reality. This study aims to determine the effect of augmented reality media on the ability to recognize Arabic vocabulary in children aged 5-6 years at TKIT Mukti Tama. This study employed a quantitative approach with a one-group pretest-posttest experimental design. The research subjects consisted of 14 children selected using a total sampling technique. Data were collected through structured observation and analyzed using a paired sample t-test with the assistance of SPSS version 25. The results showed that the data were normally distributed, with significance values of 0.080 and 0.200 (> 0.05). The hypothesis testing result showed a significance value of 0.000 < 0.05 with a t-value of -13.911, indicating a significant effect of augmented reality media on children's Arabic vocabulary recognition ability. The average score increased from 68.709 to 84.86. Therefore, it can be concluded that augmented reality media is effective in improving Arabic vocabulary recognition in early childhood.